Hospitalization of patients with nutritional anemia in the United States in 2020 - Tian, Jie; Fan, YangYang; Wei, Xin; Li, Jiangli; Yang, ZeLong; Na, Xiaolin; Zhang, Yunbo (Frontiers in Public Health, 2024)
Background Nutritional anemia is highly prevalent and has triggered a globally recognized public health concern worldwide. Objective To better understand the prevalence of anemia and the state of nutritional health in developed countries to inform global nutritional health and better manage the disease. Method We employed the Healthcare Cost and Utilization Project (HCUP)-2020 National Inpatient Health Care Data (NIS), administered by The Agency for Healthcare Research and Quality. Nutritional anemia was diagnosed according to the International Classification of Diseases, 10th Revision (ICD-10). Matching analysis and multivariate regression were used to adjust for patient and hospital characteristics. Controls were obtained by stratifying and matching for age and sex.The 2020 HCUP-NIS database encompassed a survey over 6.4 million hospitalized patients, among which 1,745,350 patients diagnosed with anemia, representing approximately 26.97% of the hospitalized population, over 310,000 were diagnosed with nutritional anemia, and 13,150 patients were hospitalized for nutritional anemia as primary diagnosis. Hospitalization rate for nutritional anemia exhibited an increased age-dependent increase nationwide, especially among females, who displayed 1.87 times higher than males. Notably, in comparison to the control group, individuals of the Black race exhibit a higher prevalence of nutritional anemia (case group: 21.7%, control group: 13.0%, P < .001). In addition, hospitalization rates were higher among low-income populations, with lower rates of private insurance (case group: 18.7%, control group: 23.5% , P < .001) and higher rates of Medicaid insurance (case group: 15.4%, control group: 13.9%, P < .001). In areas characterized by larger urban centers and advanced economic conditions within the urban-rural distribution, there was an observed increase in the frequency of patient hospitalizations. Iron deficiency anemia emerged as the predominant subtype of nutritional anemia, accounting for 12,214 (92.88%). Secondary diagnosis among patients hospitalized for nutritional anemia revealed that a significant number faced concurrent major conditions like hypertension and renal failure. Conclusions In economically prosperous areas, greater attention should be given to the health of low-income individuals and the elderly. Our findings hold valuable insights for shaping targeted public health policies to effectively address the prevalence and consequences of nutritional anemia based on a overall population health.